Online Extensive Reading: A Friend or Foe - Mevlüdiye Ucaçelik; Ahmet Şahan (Ömer Gökhan Ulum, 2023)
The study looked into the perceptions of EFL instructors working at schools of foreign languages at various universities throughout Turkey in order to better understand the effects of Online Extensive Reading (OER) on language learning and the difficulties regarding its implementation. A mixed-type descriptive study design was used to achieve the aim of the study, and the data were collected through semi-structured interviews and an online questionnaire. The questionnaire was completed by 181 EFL instructors, and 10 of them took part in the interviews. The quantitative data analysis was performed via SPSS.23 and frequencies and percentages were calculated. The qualitative data analysis which resulted in the formation of various themes and codes was carried out via MAXQDA. The results revealed that while the instructors held favourable perceptions towards the effects of OER on language learning including its benefits on reading, writing, and vocabulary, they were worried about certain difficulties including hectic schedules, student motivation, school curriculums, exams, and their technical expertise. Overall, it was concluded that despite the instructors' favourable perceptions of OER, it is not a practice that is frequently used in higher education in Turkey due to the instructors' lack of knowledge of OER and the difficulties they mentioned.